Structures of hydrogen-induced cracks under different hydrogen concentrations for a high strength steel. (October 2021) - Wang, Y.F.; Hu, S.Y.; Tian, Z.Q.; Cheng, G.X.; Zhang, Jianxiao
Highlights: The ratio of crack depth/length increases with hydrogen concentration. Variance of internal pressure responsible for the different crack structures. Crack geometry parameter defined as a useful indicator of internal pressure. Abstract: Quantitative prediction of the hydrogen-induced crack initiation remains challenging, partially due to the difficulties in directly measuring the hydrogen gas pressure in the crack cavity. Through detailed cross-sectional observations, this study shows that the structure of the internal cracks beneath the surface blisters, i.e., the ratio of crack depth/length, can be significantly influenced by the hydrogen charging conditions. This is attributed to the change of hydrogen gas pressure in the crack cavity at different hydrogen contents, supported by the formation of stepwise cracks near the specimen surface as well as the hydrogen concentration measurements. The post-failure crack geometry is considered a useful indicator of the level of internal gas pressure to quantitatively assess the hydrogen-induced cracking sensitivity. The mechanisms of crack initiation and propagation at different hydrogen concentrations are discussed.